Social media and agenda setting: implications on political agenda - Ali Salman,; Normah Mustaffa,; Mohd Azul Mohamad Salleh,; Mohd Nor Shahizan Ali, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Since the advent of the Internet, political information is now at the fingertips of every Malaysian, especially those living in the urban areas and having access to the Internet. One does not need to have the traditional media such as radio, television or Newspaper to understand what is happening in political set up in Malaysia these days. This is because the social media, especially Facebook and twitter have made access to information so easy to the larger population. The aim of this paper is to explore the role of social media as agenda setting mechanisms in the Malaysia political scenario. The study uses secondary data sources to obtain insight on the issue. It is evident from literature that the social media, especially the social media (eg. Facebook) play an important role in shaping public opinion on important political matters. The social media has been used by the public to express their concern and grievance on issues that concern their welfare which the traditional media may not dare to report or broadcast. Agenda setting needs to be relooked into as the public agenda is taking a central stage through the new/social media. Thus, it implies, the agenda setting model could be extended or remodeled to include the new/social media due to their influence on public agenda. Further implication of this is that politicians should keep abreast with the development in the social media so that they will understand current issues that are of great concern to the people and the society at large. We have to come to terms with the fact that we are now in the digital and globalised era, hence agenda setting needs to be relooked into as the public agenda is taking a central stage through the social media.